El trabajo colaborativo en las clases de educación física como estrategia de enseñanza para potenciar el aprendizaje de los estudiantes de décimo año de la unidad educativa Pio Jaramillo Alvarado periodo 2019- 2020. - Barba González, Steven Rodrigo (2020)
This research entitled: COLLABORATIVE WORK IN PHYSICAL EDUCATION CLASSES AS A TEACHING STRATEGY TO ENHANCE THE LEARNING OF TENTH YEAR STUDENTS OF UNIDAD EDUCATIVA PIO JARAMILLO ALVARADO DURING THE 2019-2020 SCHOOL YEAR. The research problem posed the following question: Will it be possible to enhance the learning of students of tenth-year “B” of Unidad Educativa “Pio Jaramillo Alvarado” in Physical Education classes applying collaborative work as a teaching strategy? The general objective stated was: To plan a pedagogical proposal applying collaborative work strategy during Physical Education classes to enhance the learning of students of tenth-year "B" of Unidad Educativa “Pio Jaramillo Alvarado”, which was scientifically focused on two variables: collaborative work, dependent variable, and the strategy, independent variable. The research focus is mixed, the research type is correlational, and the design of the research is quasi-experimental. For the development of this research work different methods were used, such as: inductive, deductive, analytical-synthetic and statistical methods. Likewise, for data collection, research techniques and instruments such as survey (questionnaire), observation (observation guide), interview (interview guide) and the test (collaborative work test), were applied to determine the teaching-learning processes in the Physical Education classes. After applying the pedagogical proposal taking into account collaborative work strategy, 100% of the students managed to enhance their learning, so that it is recommended to apply the collaborative work strategy in Physical Education classes to improve the teaching-learning processes.